Beyond Ideological Cleavages: A Unifying Framework for Industrial Policies and Other Public Interventions - Benhassine, Najy; Raballand, Gael (2012)
This paper introduces a new framework to characterize the diversity of public policies and interventions to spur investment and growth. Going beyond ideological cleavages on this topic, we argue that two orthogonal features determine how much interventions depart fundamentally from neutral policies: (1) their degree of selectivity (in terms of sectors or other targeted categories of firms) and (2) the extent of price subsidies embedded in such interventions. These two characteristics of interventions respond to different types of justifications, and they do not necessarily need to go hand in hand, even if they often do in practice. Depending on their selectivity and/or the extent of price subsidies, interventions are shown to vary in their distortions, their benefits, and their opportunity costs. The framework is used to illustrate how different country characteristics affect these pros and cons of interventionism. In particular, we look at the effects of the initial state of the investment climate, the country's institutional capacity, its political economy context and the nature of the State-business interaction. Using the examples of poor countries with a small undiversified industrial base, we show that it is often in the situations where interventions may be the most needed, that the conditions for their success are likely to be the weakest, which does not mean either that some interventions cannot succeed in low-income countries.